Post-Vaccination Yellow Fever Antiserum Reduces Zika Virus in Embryoid Bodies When Placental Cells are Present - Emily M. Schultz; TyAnthony J. Jones; Hannah K. Hopkins; Jingmei Zeng; Kelli L. Barr (Vaccines, 2020)
Zika virus (ZIKV) is a flavivirus that originated in Africa but emerged in Latin America in 2015. In this region, other flaviviruses such as Dengue (DENV), West Nile, and Yellow Fever virus (YFV) also circulate, allowing for possible antigenic cross-reactivity to impact viral infections and immune responses. Studies have found antibody-mediated enhancement between DENV and ZIKV, but the impact of YFV antibodies on ZIKV infection has not been fully explored. ZIKV infections cause congenital syndromes, such as microcephaly, necessitating further research into ZIKV vertical transmission through the placental barrier. Recent advancements in biomedical engineering have generated co-culture methods that allow for the in vitro recapitulation of the maternal–fetal interface. This study utilized a transwell assay, which was a co-culture model utilizing human placental syncytiotrophoblasts, fetal umbilical cells, and a differentiating embryoid body, to replicate the maternal–fetal axis. To determine if cross-reactive YFV vaccine antibodies impacted the pathogenesis of ZIKV across the maternal–fetal axis, syncytiotrophoblasts were inoculated with ZIKV or ZIKV incubated with YFV vaccine antisera, and the viral load was measured 72 h post-inoculation. Here, we report that BeWo and HUVEC cells were permissive to ZIKV and that the impact of YFV post-vaccination antibodies on ZIKV replication was cell line-dependent. Embryoid bodies were also permissive to ZIKV, and the presence of YFV antibodies collected 4–14 months post-vaccination reduced ZIKV infection when placental cells were present. However, when directly infected with ZIKV, the embryoid bodies displayed significantly increased viral loads in the presence of YFV antiserum taken 30 days post-vaccination. The data show that each of the cell lines and EBs have a unique response to ZIKV complexed with post-vaccination serum, suggesting there may be cell-specific mechanisms that impact congenital ZIKV infections. Since ZIKV infections can cause severe congenital syndromes, it is crucial to understand any potential enhancement or protection offered from cross-reactive, post-vaccination antibodies.